2021
DOI: 10.3390/v13071396
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA Metagenomics of Hyalomma Ticks Collected from Dromedary Camels in Makkah Province, Saudi Arabia

Abstract: Arthropod-borne infections are a medical and economic threat to humans and livestock. Over the last three decades, several unprecedented viral outbreaks have been recorded in the Western part of the Arabian Peninsula. However, little is known about the circulation and diversity of arthropod-borne viruses in this region. To prepare for new outbreaks of vector-borne diseases, it is important to detect which viruses circulate in each vector population. In this study, we used a metagenomics approach to characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
2
23
1
Order By: Relevance
“…Our finding is agreeing with Hoffman et al, 2018 66 and Horton et al, 2016 67 who reported that 0.66% and 0.36% were detected as AHFV, respectively. However, Zakham et al, 2021 68 found that AHFV represent 10% of all collected samples in Saudi Arabia and these results may be attributed to the transportation of thousands of animals yearly out of Africa and other countries to Mecca, Saudi Arabia, in order to fulfill the individual need for diet and transportation during the Hajj 69 . Carletti et al 2010 confirm the existence of AHFV in Egypt as it was detected in two tourists returning back to Italy from southern Egypt 40.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding is agreeing with Hoffman et al, 2018 66 and Horton et al, 2016 67 who reported that 0.66% and 0.36% were detected as AHFV, respectively. However, Zakham et al, 2021 68 found that AHFV represent 10% of all collected samples in Saudi Arabia and these results may be attributed to the transportation of thousands of animals yearly out of Africa and other countries to Mecca, Saudi Arabia, in order to fulfill the individual need for diet and transportation during the Hajj 69 . Carletti et al 2010 confirm the existence of AHFV in Egypt as it was detected in two tourists returning back to Italy from southern Egypt 40.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has contributed to this development with the Lazypipe mNGS pipeline designed primarily for virus discovery from clinical, animal and environmental samples with minimal requirements in terms of bioinformatic expertise and/or resources [ 22 ]. Lazypipe has been adopted as a standard module for mNGS analysis at the Finnish IT Center for Science ( , accessed on 21 December 2022) and has been successfully applied to detect and characterize a multitude of novel viral pathogens from a variety of different sample types, including arthropod vectors [ 23 , 24 ], mosquitos [ 25 ], farm animals [ 26 ] and wildlife [ 27 ]. Here, we present an enhanced version of our mNGS pipeline, Lazypipe 2.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the majority of field surveillance studies of tick-associated microbes focus on the causative agent of Lyme disease Borrelia burgdorferi and a select number of other known human pathogens, such as Rickettsia (Rocky Mountain spotted fever and other Rickettsioses), Anaplasma phagocytophilium (Anaplasmosis), and Powassan virus. Although the full diversity of microbes carried by ticks is much greater than those definitively linked to human disease [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] , we know strikingly little about the ecology or disease implications of most tickassociated microbes. Furthermore, we are only beginning to appreciate the broader role microbes play in tick biology.…”
Section: Introductionmentioning
confidence: 99%